Review of Access to Financing in the Credit Tranches and Under the Extended Fund Facility, and Overall Access Limits Under the General Resources Account. (Policy Papers; Policy Paper ;, 2008)
The Board completed its last review of access policy in February 2008 (2008 Access Policy Review). At that time, while some Directors saw the need for an increase in the limits on normal access to Fund resources, most Directors supported maintaining the access limits in the credit tranches and under the Extended Fund Facility (EFF) and the separate overall limits on access to resources in the General Resources Account (GRA) at the present level of 100 percent of quota on an annual basis and 300 percent on a cumulative basis. During the 2008 Spring Meetings, the International Monetary and Financial Committee (IMFC) encouraged the Executive Board to consider raising access limits. In doing so, the IMFC recognized that emerging market and developing countries are not immune to a broadening of the problems in financial markets and looked forward to reviewing progress at its next meeting. A fresh look at access limits is warranted in light of the broader review of the Fund's lending framework which is underway, and to take account of the April 28, 2008 agreement on a second round of ad hoc quota increases under the quota and voice reform.